دراسة تحليلية عن مشكلات قراءة النصوص العربية لطالبات المدرسة المتوسطة الإخوان توفويو - Nur Fadilah Amin; Sarah Mutmainnah Putri; Darmawati (Naskhi: Jurnal Kajian Pendidikan dan Bahasa Arab, 2023)
This study aims to determine difficulty of reading Arabic texts, determine the supporting and inhibiting factors in reading Arabic texts, and Find out the teacher's efforts in overcoming the difficulties of Eighth Grade Students of Madrasah Tsanawiyah Al-Ikhwan Topoyo, Mamuju Tengah, West Sulawesi in reading Arabic texts. This study uses a qualitative approach with interview, observation and documentation as data collectiob methode. The results of this study indicate that in reading Arabic texts, the difficulties that are often experienced by students are: 1) Linguistic difficulties which include aswat difficulties, difficulties in how to read harakat fathah, kasroh, and dommah. Students also have difficulty in vocabulary because of the lack of memorization of mufrodat, and the last is difficulty in terms of meaning. 2) Supporting factors in reading Arabic texts are if the students live in dormitories and students' interest in learning is quite high, while the inhibiting factors are teaching methods that are less varied, media or infrastructure that is not complete. 3) The efforts made by the teacher to overcome the problem are trying new breakthroughs such as alternative methods, then the teacher also tries to always motivate and encourage students to like Arabic, as well as implementing the routine of reading the Qur’an before lessons start.